A NEW APPROACH FOR THE DEVELOPMENT AND MANAGEMENT OF BRACKISH KARST SPRINGS - Maramathas A. (My University, 2006)
A new approach to the method of artificial upraising of the water outlet point, for management and development of brackish karst springs, uses the MODKARST model. Brackish karst springs simulation can be used to estimate the necessary upraising of the spring elevation, so that sea-water intrusion is blocked. The consequent freshwater loss to the sea, due to this upraising, can also be estimated. The method has been applied to the periodically brackish karst Almiros spring at Heraklion of Crete, Greece. The spring simulation showed that the sea-water intrusion could be prevented through an artificial upraising of the water-outlet point, realized by the construction of a dam. The exact upraising has been estimated. Freshwater loss to the sea because of this upraising has also been estimated. The model could also be used as a tool for the management of the spring. For example, it was used to assess management options for the spring during the depletion period of the year 1994. The best scenario for the development of the spring during this period has been estimated.
Keywords: KARST; SALINIZATION; SALT-WATER/FRESH-WATER RELATIONS; GROUNDWATER DEVELOPMENT; GROUNDWATER MANAGEMENT